Isokinetic values in closed kinetic chain in young adults - Pavel Loeza-Magaña; Viridiana Reyes-Bello; Héctor Ricardo Quezada-González; Pedro Iván Arias-Vázquez (Elsevier, 2024)
Objective: To describe the values of isokinetic strength in closed kinetic chain (CKC) in young adults and their reproducibility. Methods: Test and re-test in isokinetic leg press, unilateral mode at 0.1 m/s and 0.3 m/s, 2 sets of 10 repetitions at each speed was performed. Results: 30 men and 22 women were included. The isokinetic values show differences between men and women. The intraclass correlation coefficient was >0.88 (p < 0.001) except in flexors (women), 0.74. Conclusion: The CKC isokinetic test is valid, reproducible, and safe.